Prediksi Gratitude terhadap Body Image pada Remaja di Indonesia - Valerinne Audrylia Susanto; Ferdian, Flaviana Rinta (Atma Jaya Catholic University of Indonesia, 2025)
Body image is a critical aspect of adolescent development because the physical changes often trigger feelings of dissatisfaction, which increase the risk of developing a negative body image. A negative body image can lead to various adverse effects, such as feelings of inferiority, difficulty in self-acceptance, and even mental health problems. These can be mitigated by fostering a more positive body image through the practice of gratitude. High levels of gratitude can help adolescents accept their bodies better by focusing on positive aspects. Therefore, this study aims to examine the predictive role of gratitude on body image among adolescents. This quantitative study involved 455 adolescent participants aged 13-18 years residing in Indonesia. Data were collected using a non-probability sampling technique, specifically convenience sampling. The instruments used were the Multidimensional Body-Self Relations Questionnaire-Appearance Scales (MBSRQ-AS) and the Skala Bersyukur Indonesia (SBI). This study employed a correlational design with simple linear regression statistical techniques for data analysis. The research results indicate that gratitude can significantly predict body image in adolescents. Additional findings reveal a negative relationship between Body Mass Index (BMI) and body image. To gain a deeper understanding of these two variables, future researchers may consider external factors that can influence body image, such as social media, family, or peers.